2019
DOI: 10.18203/issn.2454-5929.ijohns20193874
|View full text |Cite
|
Sign up to set email alerts
|

A study of auditory brainstem evoked responses in type 1 and type 2 diabetes mellitus patients with normal hearing

Abstract: <p class="abstract"><strong>Background:</strong> Diabetes mellitus (DM) is one of the most common metabolic disorders with millions of cases world-wide. Its effect on functioning of the central nervous system (CNS) and the peripheral nerves is a matter of current neurological research. Our study aimed to find out changes in auditory brainstem responses if any, in patients with type 1 and type 2 DM patients with apparently normal hearing.</p><p class="abstract"><strong>Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…A study conducted by Goyal et al in 2019 on auditory brainstem evoked responses in type 1 and type 2 DM patients concluded that there was no hearing loss among type 1 diabetic mellitus patients, but a significant delay in absolute latency of wave I, III, IV, and V and interpeak latencies I-V and III-V was seen in type 1 diabetic patients. No relation was found with the duration of diabetes [6]. There are few studies with similar results, where the children with type 1 DM had no sensorineural hearing loss, but the latency of the waves were prolonged compared to the control group [6,7].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A study conducted by Goyal et al in 2019 on auditory brainstem evoked responses in type 1 and type 2 DM patients concluded that there was no hearing loss among type 1 diabetic mellitus patients, but a significant delay in absolute latency of wave I, III, IV, and V and interpeak latencies I-V and III-V was seen in type 1 diabetic patients. No relation was found with the duration of diabetes [6]. There are few studies with similar results, where the children with type 1 DM had no sensorineural hearing loss, but the latency of the waves were prolonged compared to the control group [6,7].…”
Section: Discussionmentioning
confidence: 86%
“…No relation was found with the duration of diabetes [6]. There are few studies with similar results, where the children with type 1 DM had no sensorineural hearing loss, but the latency of the waves were prolonged compared to the control group [6,7]. Some studies…”
Section: Discussionmentioning
confidence: 96%
“…A significant delay in the absolute latency of waves I, II, III, IV and V and interpeak latencies (IPLs) of waves I-III, I-V and III-V was observed in DM2 individuals. 37 Other studies 38 39 with DM2 patients and healthy controls have reported a significant increase in the absolute latencies of waves I, III and V and IPLs of waves III-V and I-V. Kannan 40 also reported an increase in both absolute latencies (of waves III and V) and IPLs (of waves I-III, I-V and III-V) in DM2 individuals compared with healthy controls. Studies 41 42 reporting the effect of stimulus intensity on AEPs in DM2 revealed a significant increase in the absolute latencies of waves III and V and IPLs of waves I-III, III-V and I-V at 70 dBnHL and 80 dBnHL, whereas, at 90 dBnHL, the authors found a significant increase in the absolute latency of wave I compared with that of the other two intensities.…”
Section: Resultsmentioning
confidence: 92%
“…It can be inferred from the aforementioned findings, that DM2 can result in reduced conduction velocity in the auditory nerve that occurs secondary to diabetic neuropathy. Some authors [37][38][39][40] suggest that the prolongation of wave I could be due to a reduction in the time of peripheral transmission, and that the prolongation of waves III and V could be due to a reduction in the time of central transmission. This can be attributed to the neuronal degeneration that results from the oxidative stress and apoptosis of neurons in DM2.…”
Section: Audiological Evaluation In Type-2 Diabetes Mellitusmentioning
confidence: 99%